Up‐regulation and activation of the P2Y2 nucleotide receptor mediate neurite extension in IL‐1β‐treated mouse primary cortical neurons. (25th April 2013) - Peterson, Troy S.; Thebeau, Christina N.; Ajit, Deepa; Camden, Jean M.; Woods, Lucas T.; Wood, W. Gibson; Petris, Michael J.; Sun, Grace Y.; Erb, Laurie; Weisman, Gary A.
Abstract The pro‐inflammatory cytokine interleukin‐1β (IL‐1β), whose levels are elevated in the brain in Alzheimer's and other neurodegenerative diseases, has been shown to have both detrimental and beneficial effects on disease progression. In this article, we demonstrate that incubation of mouse primary cortical neurons (mPCNs) with IL‐1β increases the expression of the P2Y2 nucleotide receptor (P2Y2R) and that activation of the up‐regulated receptor with UTP, a relatively selective agonist of the P2Y2R, increases neurite outgrowth. Consistent with the accepted role of cofilin in the regulation of neurite extension, results indicate that incubation of IL‐1β‐treated mPCNs with UTP increases the phosphorylation of cofilin, a response absent in PCNs isolated from P2Y2R−/− mice. Other findings indicate that function‐blocking anti‐αvβ3/5 integrin antibodies prevent UTP‐induced cofilin activation in IL‐1β‐treated mPCNs, suggesting that established P2Y2R/αvβ3/5 interactions that promote G12‐dependent Rho activation lead to cofilin phosphorylation involved in neurite extension. Cofilin phosphorylation induced by UTP in IL‐1β‐treated mPCNs is also decreased by inhibitors of Ca2+/calmodulin‐dependent protein kinase II (CaMKII), suggesting a role for P2Y2R‐mediated and Gq‐dependent calcium mobilization in neurite outgrowth. Taken together, these studies indicate that up‐regulation of P2Y2Rs in mPCNs under pro‐inflammatory conditions can promote cofilin‐dependent neurite outgrowth, a neuroprotective response that may be a novel pharmacological target in the treatment of neurodegenerative diseases.